Characterization of Individual Projections Reveal That Neuromasts of the Zebrafish Lateral Line are Innervated by Multiple Inhibitory Efferent Cells - Remy Manuel; Ana Belen Iglesias Gonzalez; Judith Habicher; Harmen Kornelis Koning; Henrik Boije (Frontiers Media S.A., 2021)
The zebrafish lateral line is a sensory system used to detect changes in water flow. It is comprized of clusters of superficial hair cells called neuromasts. Modulation occurs via excitatory and inhibitory efferent neurons located in the brain. Using mosaic transgenic labeling we provide an anatomical overview of the lateral line projections made by individual inhibitory efferent neurons in 5-day old zebrafish larvae. For each hemisphere we estimate there to be six inhibitory efferent neurons located in two different nuclei. Three distinct cell types were classified based on their projections; to the anterior lateral line around the head, to the posterior lateral line along the body, or to both. Our analyses corroborate previous studies employing back-fills, but our transgenic labeling allowed a more thorough characterization of their morphology. We found that individual inhibitory efferent cells connect to multiple neuromasts and that a single neuromast is connected by multiple inhibitory efferent cells. The efferent axons project to the sensory ganglia and follow the sensory axon tract along the lateral line. Time-lapse imaging revealed that inhibitory efferent axons do not migrate with the primordium as the primary sensory afferent does, but follow with an 8-14 h lag. These data bring new insights into the formation of a sensory circuit and support the hypothesis that different classes of inhibitory efferent cells have different functions. Our findings provide a foundation for future studies focussed toward unraveling how and when sensory perception is modulated by different efferent cells.